The role of emotional intelligence on the level of understanding of students majoring in sharia accounting with learning behavior as moderation - zumnia, sofwa`; Nurfitriana , Amesti Eka; Hidayati, Tri Nur (Islamic Accounting Journal, 2024)
The aim of this research is to determine the influence of emotional intelligence on the level of accounting understanding and the moderating influence of learning behavior on emotional intelligence on the level of accounting understanding. Sample selection used a purposive sampling technique of 40 samples. Data testing uses multiple linear regression analysis with SPSS tools. Data for the level of understanding of accounting is proxied by a questionnaire that is in accordance with the main accounting courses in the Sharia Accounting strata-1 program at the Salatiga State Islamic Institute. Data on learning behavior and emotional intelligence were collected through questionnaires. The results of the multiple linear regression analysis test show that the emotional intelligence variable has a significant positive effect on the level of accounting understanding. And the existence of a moderating variable, namely learning behavior, strengthens the influence of emotional intelligence on students’ level of accounting understanding.